PENGARUH GAYA KEPEMIMPINAN DAN MOTIVASI KERJA TERHADAP KEPUASAN KERJA DAN IMPLIKASINYA PADA KINERJA PEGAWAI BANK PERKREDITAN RAKYAT - Nuniek Permata; Furtasan Ali Yusuf; Basrowi Basrowi (LP2M Universitas Bina Bangsa, 2023)
The goal to be achieved through this research is to find direct and indirect effects between leadership steal and motivation on employee performance both directly and through the interveing ​​variables of employee job satisfaction at PT BPR (Perseroda) Serang district. The research design is structural equation modeling (SEM) which places the variables of leadership style and work motivation as exogenous variables, performance as endogenous variables, and job satisfaction as intervening variables. The research population was 221 people. The sampling technique uses a proportional stratification random sampling technique. The sample size is 200 respondents. Primary data was collected using a questionnaire. Secondary data was collected using the documentation method. Data were analyzed using smart PLS software. The results of the analysis show that there are four significant hypotheses, and one hypothesis that is not significant. Based on the results of the hypothesis testing the majority of the hypotheses were accepted, there was only one hypothesis, namely the third hypothesis which was rejected. Thus the theoretical model is actually proven empirically, although there is one hypothesis that is rejected